Can innovations in logistics and financial services benefit actors throughout agricultural value chains? - Ambler, Kate; Bloem, Jeffrey R.; de Brauw, Alan; Maruyama, Eduardo (CGIAR System Organization, 2022)
Catalyzed by changes to global markets, urbanization, and other trends, agri-food value chains have been growing and changing rapidly in low- and middle-income countries (LMICs) over the past few decades. Perhaps more than ever, even in the world’s poorest countries, farmers can access high-value consumer markets both domestically and abroad. Benefiting from access to these high-value markets, however, often requires that crops meet specific quality, reliability, and volume standards. However, smaller agri-food value chain actors—farmers, aggregators, traders, processors or others—may not operate at a large enough scale to make traditional investments required to meet those standards, therefore hindering their ability to participate in new, more remunerative markets.